2013
DOI: 10.1093/ndt/gfs585
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival among sickle cell kidney transplant recipients in the recent era

Abstract: Patient survival has improved among contemporary sickle cell recipients compared with an earlier cohort and is comparable to a matched cohort of diabetic kidney recipients. Appropriately selected SCD patients may receive kidney transplants with reasonable survival outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 19 publications
3
34
0
Order By: Relevance
“…44 Further, although the post-renal-transplantation survival discrepancy still exists between SCD and non-SCD patients with ESRD, the overall mortality for SCD patients posttransplantation has improved and is now comparable with patients with diabetes. 46 Once a patient is listed for renal transplantation, s/he should be started on regular blood transfusion (preferably EBT), which improves their well-being and fitness for surgery while awaiting transplantation. Patients on regular EBT posttransplantation have better graft survival and fewer adverse events, including painful crises and acute sickle nephropathy.…”
Section: Renal Replacement Therapymentioning
confidence: 99%
“…44 Further, although the post-renal-transplantation survival discrepancy still exists between SCD and non-SCD patients with ESRD, the overall mortality for SCD patients posttransplantation has improved and is now comparable with patients with diabetes. 46 Once a patient is listed for renal transplantation, s/he should be started on regular blood transfusion (preferably EBT), which improves their well-being and fitness for surgery while awaiting transplantation. Patients on regular EBT posttransplantation have better graft survival and fewer adverse events, including painful crises and acute sickle nephropathy.…”
Section: Renal Replacement Therapymentioning
confidence: 99%
“…An investigation of outcomes in recipients of renal allografts in the United States revealed that 1-year cadaveric renal allograft survival in recipients with sickle-cell nephropathy was comparable to that in patients with end-stage renal disease from other causes but was significantly poorer at 3 or 6 years. 26,27 Additionally, 6-year survival among recipients with SCD was 71%, compared with 84% for the matched cohort with other diagnoses, and was associated with a 3.42-fold increased risk of death. The etiology of mortality was thought to be mainly due to underlying SCD.…”
Section: Sot In Scdmentioning
confidence: 99%
“…Table 3 lists the publications on SOT for patients with SCD. To date, kidney, [25][26][27] liver, [28][29][30] lung, 31 and combined heart-kidney 32 and liver-kidney 33 transplantations have been reported, with kidney transplantation being the most common. An investigation of outcomes in recipients of renal allografts in the United States revealed that 1-year cadaveric renal allograft survival in recipients with sickle-cell nephropathy was comparable to that in patients with end-stage renal disease from other causes but was significantly poorer at 3 or 6 years.…”
Section: Sot In Scdmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study using the Organ Procurement and Transplanting Network/ United Network for Organ Sharing data, investigators showed improvements in 6 year kidney transplant outcomes in recent years (2000-2011) compared to prior years (1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999) with results similar to those seen for patients with diabetes who received transplants. 29 RN is a 22-year-old with hemoglobin SC disease who presents to the ED with SOB and chest pain. She reports that she was studying for her physics final and had been spending lots of time sitting in the library.…”
mentioning
confidence: 99%